Central Asian Countries on the Path of Regional Cooperation (Eurasian Journal of Humanities and Social Sciences, 2023)
In this article, the opinions of the peoples of Central Asia about the need for mutual economic, political and cultural relations are described. The reason is that the peoples of this region have always lived together. These processes are developing more rapidly in recent times.